2020
DOI: 10.3390/ijms22010236
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Epigenome in Nuclear Transfer Cloning: Where, When and How

Abstract: The nucleus of a differentiated cell can be reprogrammed to a totipotent state by exposure to the cytoplasm of an enucleated oocyte, and the reconstructed nuclear transfer embryo can give rise to an entire organism. Somatic cell nuclear transfer (SCNT) has important implications in animal biotechnology and provides a unique model for studying epigenetic barriers to successful nuclear reprogramming and for testing novel concepts to overcome them. While initial strategies aimed at modulating the global DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 159 publications
0
14
0
Order By: Relevance
“…Pluripotency transcriptional factors (POU5F1, NANOG, and SOX2) were correlated with low DNA methylation levels in epigenetic regulation. DNA methylation and histone modification suggest a vital role for SCNT embryos (Simmet et al, 2020; Wang et al, 2020). Studies have shown that miRNAs are identified in oviductal EVs (oEVs), and potential target genes are involved in embryo development (Almiñana & Bauersachs, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pluripotency transcriptional factors (POU5F1, NANOG, and SOX2) were correlated with low DNA methylation levels in epigenetic regulation. DNA methylation and histone modification suggest a vital role for SCNT embryos (Simmet et al, 2020; Wang et al, 2020). Studies have shown that miRNAs are identified in oviductal EVs (oEVs), and potential target genes are involved in embryo development (Almiñana & Bauersachs, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…X-inactivation in mammals is still a topic with open questions and species-specific differences were reported [ 196 , 197 ]. In cloned embryos, abnormal development in both sexes was shown and a connection to variations in X-inactivation was established (reviewed in [ 97 ]). These differences between sexes and the effect of in vitro culture on kinetics and epigenetic reprogramming must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Problems occurring when conducting SCNT are micromanipulation trauma, oocyte incompetence, in vitro culture-induced anomalies and failed epigenetic reprogramming of the transferred nucleus (reviewed in [ 96 ]). As a result, physiological development is considered to be impaired as abnormal epigenetic profiles and gene expression may occur (reviewed in [ 97 ]). After transfer of bovine SCNT embryos to recipients, placental failure has frequently been observed, likely due to abnormal embryo-maternal communication during peri-implantation [ 98 , 99 ], giving a possible explanation for the high rate of pregnancy failures.…”
Section: State Of the Art—assisted Reproductive Technologies In Cattle And Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many transgenic pigs have been created, the cloning efficiency remains extremely low due to a low rate of full-term development, and high rates of pregnancy loss and fetal abnormalities (Wilmut et al, 2002;Whitworth and Prather, 2010;Chavatte-Palmer et al, 2012). Increasing evidence suggests that incomplete epigenetic reprogramming of the donor cell (in terms of DNA methylation and histone methylation/acetylation) causes low cloning efficiency (Dean et al, 2001;Matoba and Zhang, 2018;Simmet et al, 2020;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%